CASES SIMILAR AND DIFFERENCES UZBEK AND ENGLISH (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Abstract:. A conjunction is a grammatical form that shows the relationship of a noun or noun to other words. Being a noun, it indicates that it is subordinate to another word in a compound or sentence.